HUBUNGAN POLA ASUH ORANG TUA DENGAN MOTIVASI BELAJAR PADA ANAK SEKOLAH KELAS V DI SDN KERONCONG MAS PERMAI KECAMATAN JATI UWUNG KOTA TANGERANG - Ria setia sari; yuliana yuliana; whindi windi (Universitas Yatsi Madani, 2019)
Motivation of the study is inclination for student to study that stimulate by desire to reach achievement or the result as good as possible. In case will influence by parents’ educating which is open and always available time that will help children to understand their self who always changing also will help children to influence their spirit of study. The objective of the research is to know the correlation between parents’ educating and motivation study on Fifth grade students at SDN Keroncong Mas Permai Kecamatan Jatiuwung Kota Tangerang on 2015. The method in this research use correlation descriptive which is to know correlation two variables between parents’ educating and motivation of study. The technique of sample is purposive sampling. The sample use 93 responders on elementary student. The instrument use questioner form which is contain some questions. Technique analyzing the data use analysis unvariat and bivariat. This result of research show the value p=0,038 which is value <from ɑ =0,05with hypothesis Ho refuse means there is correlation between parents’ educating and motivation of study on Fifth grade students at SDN Keroncong Mas Permai Kecamatan Jatiuwung Kota Tangerang on 2015. Suggestion for parents is more perspective to children in their studying especially how to good educate to motivating student in the study.